The strategies Used by Primary School English Teachers in Teaching Third Grade Children - Boukhadia, Hind (My University, 2024)
In recent years, there has been a growing interest in understanding the strategies employed by English teachers in teaching young learners. This study aims to investigate the various strategies used by primary teachers to facilitate language learning among third grade children. Based on an observational data collected from two English classes at primary schools, a thematic analysis was conducted. The analysis uncovered several key strategies employed, such as songs, drills, Visual aids, storytelling, games, and realia. Applying these strategies successfully captivated the attention of young students and improved their comprehension and memory retention of concepts, with effectiveness varying according to students’ learning preferences, cognitive capacities, and cultural background. These results provide insights into pedagogical strategies that can aid in fostering early language development in young learners.
Keywords: primary English teachers; young learners; strategies used